Searching large-scale scRNA-seq databases via unbiased cell embedding with Cell BLAST - Zhi-Jie Cao (Nature Portfolio, 2020)
Single-cell RNA-seq (scRNA-seq) is being widely used to resolve cellular heterogeneity. Here, the authors present a cell-querying method built on a neural network-based generative model and a customized cell-to-cell similarity metric.